Studi Rugi Daya Pada Transformator 20 KV/690 VOLT Pada Industri Kertas Saat Terjadi Gangguan 1 Phasa Ke Tanah - Sitanggang, Van Den Bosh; Ervianto, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Energy Losses is the Loss of Electrical energy , when it is generated and supplied through end user, thereby reducing the amount of energy that can be consumed by lumped Load is the main object of this study. Normally electrical system which is supplied from Turbine Generator, transmitted, distributed to load well, but at the time a fault arise, protective system ideally working as well as designed. In this research, assumption is taken into account when short circuit occurred ,protective system is not well- working and by doing this researcher analyze, simulate by program software ETAP 12.6.0 and calculating the losses of power that?s emerging in Transformator. By analyzing the simulation and calculation by using Kirchoff?s Current Law and the Software it is hoped all parameter contribute to the conclusion and suggestion such as the ideal set point of protective system, the chosen value of reactance and resistance of the conductor and cooling system in transformator.By getting data parameter from field that Voltage supplied 20 KV/690Volt, 3150 KVA, 2635,72 Amp of Distribution Transformer , got faulted current for 0.3 km distance fault. Iph-G = 1853,5 Amp the magnitude of power losses caused by the fault is about 13.567 Watt power.Keywords : A phase- ground fault, Power losses, Transformator capacity,